Professional training of students by means of teaching reading in large classes model - M. Ashraf; R. A. Memon; A. Ahmed; V. D. Shevchenko (Вестник Самарского университета: История, педагогика, филология)
The students of Sindh University, Campus Dadu have a generally low level of English competence, notably in reading. This is primarily due to the large number of students in each class, more than sixty. The study aims to learn more about large courses and the teaching of reading in those classes in order to better understand and analyze the difficulty of teaching reading in large classes. This study is qualitative research. Simple convenient random data were collected via interviews, observations and field notes. Six teachers were interviewed and twelve classes were observed, each class of 50 minutes totaling 10 hours. Besides, field notes were taken and twenty-five students were interviewed. Coleman created a coding system that was used to examine the data in his investigation into huge classes in Indonesia. The educational environment of Sindh University is similar to that in Indonesia. The information was thematically examined. According to the data, the primary issue is class size, which encourages professors to take a dominant position and leaves pupils mostly passive. Observations of the classes showed that the professors carried out and explained the reading, while the pupils only remained on the receiving end. The teachers continued to have authority over the text. Further evidence from the study points to teachers’ ignorance of reading theories and instructional strategies. Additionally, this calls for assessing the class size, upgrading the instructional materials, and giving teachers professional development opportunities. All public sector degree-awarding institutions where the large class phenomena is popular would benefit from the study’s findings.